A Nonlinear Finite Volume Scheme Preserving Maximum Principle for Diffusion Equations (Communications in Computational Physics, 2021)
In this paper we propose a new nonlinear cell-centered finite volume schemeon general polygonal meshes for two dimensional anisotropic diffusion problems,which preserves discrete maximum principle (DMP). The scheme is based on the so-called diamond scheme with a nonlinear treatment on its tangential flux to obtain alocal maximum principle (LMP) structure. It is well-known that existing DMP preserving diffusion schemes suffer from the fact that auxiliary unknowns should be presented as a convex combination of primary unknowns. In this paper, to get rid ofthis constraint a nonlinearization strategy is introduced and it requires only a second-order accurate approximation for auxiliary unknowns. Numerical results show thatthis scheme has second-order accuracy, preserves maximum and minimum for solutions and is conservative.